Red thread of fate - Butler, Lyn Liao (Berkley, 2022)
"In the wake of a tragedy and fueled by guilt from a secret she's kept for years, a woman discovers how delicate the thread that binds family is in this powerful novel by Lyn Liao Butler. Two days before Tam and Tony Kwan receive their letter of acceptance for the son they are adopting, Tony and his estranged cousin Mia are killed in an accident. A shellshocked Tam learns she is named the guardian to Mia's five-year-old daughter, Angela. Tam has no choice but to agree to take in the girl she hasn't seen since she was a baby. With her life completely upended, Tam must also decide if she will complete the adoption on her own and bring home the son waiting for her in a Chinese orphanage. But when her secret comes to light just as she and Angela start to bond, their fragile family is threatened. As Tam uncovers the events of the past, she discovers the true meaning of love; the one she is meant to be with, and the family she is meant to have, however unlikely"--